Novel drug-inducible CRISPRa/i systems for rapid and reversible manipulation of gene transcription - Ming Sui; Meiling Zhou; Mengge Cui; Huan Liu; Xiaolin Zhang; Na Hu; Yang Li; Beibei Wang; Guojun Yang; Pengling Gui; Lingqiang Zhu; Feng Wan; et al. (Cellular and Molecular Life Sciences, 2025)
Abstract CRISPR activation and interference (CRISPRa/i) are highly effective tools to regulate transcription by fusing dead Cas9 (dCas9) with transcriptional regulatory factors guided by small guide RNA (sgRNA) in mammalian cells and mice. Still, a controllable gene regulation system is desired to investigate and manipulate dynamic biological processes. Here, we reported flexible drug-responsive CRISPRa/i systems by fusing mutated human estrogen receptor (ERT2) domains, which responded to estrogen analogue tamoxifen or its active metabolite 4-hydroxy-tamoxifen (4OHT), to CRISPRa/i components for transcriptional regulation. Upon 4OHT treatment, the optimal variants, ERT2-ERT2-CRISPRa/i-ERT2 (iCRISPRa/i), showed rapid protein translocation of iCRISPRa/i from cytoplasm to nucleus and subsequent transcriptional response. The inducible transcriptional manipulation could be restored to its original level when 4OHT was withdrawn. Moreover, the efficiencies of gene expression regulation of iCRISPRa/i were comparable to those of non-inducible and doxycycline-inducible counterparts, with a lower leakage and a faster drug response activity. The iCRISPRa/i systems successfully induced phenotypic changes in various cell lines. These results highlight that iCRISPRa/i systems could achieve fast and flexible drug-responsive transcriptional modulation and phenotypic changes, and thus provide better options for gain- and loss-of-function model construction and gene therapy.